Transient tyrosinemia of the newborn - Hasanoğlu, Alev; Özalp, İmran (The Turkish Journal of Pediatrics, 1978)
The serum tyrosine levels of 50 premature and 150 full-term infants have been assessed in order to find out the prevalence of transient tyrosinemia. 2.6 % of full-term infants and 38 % of premature infants were observed to have increased serum tyrosine levels.